2017
DOI: 10.3390/ma10030266
|View full text |Cite
|
Sign up to set email alerts
|

BPPO-Based Anion Exchange Membranes for Acid Recovery via Diffusion Dialysis

Abstract: To reduce the environmental impact of acids present in various industrial wastes, improved and robust anion exchange membranes (AEMs) are highly desired. Moreover, they should exhibit high retention of salts, fast acid permeation and they should be able to operate with low energy input. In this work, AEMs are prepared using a facile solution-casting from brominated poly-(2,6-dimethyl-1,4-phenylene oxide) (BPPO) and increasing amounts of 2-phenylimidazole (PI). Neither quaternary ammonium salts, nor ionic liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…Figure 7 b depicts the separation factor of the fabricated functionalized inorganic/organic composite AEMs at ambient temperature. The obtained value of separation factor was increased from 139 to 260 with increasing the amount of inorganic filler from 2.5% to 7.5% into the QPPO, which surpassed the evaluated commercial membrane DF-120B (24.3) [ 32 , 42 ]. With increasing the amount of inorganic filler, water uptake, linear swelling ratio (dimensional stability), and IEC were increased.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Figure 7 b depicts the separation factor of the fabricated functionalized inorganic/organic composite AEMs at ambient temperature. The obtained value of separation factor was increased from 139 to 260 with increasing the amount of inorganic filler from 2.5% to 7.5% into the QPPO, which surpassed the evaluated commercial membrane DF-120B (24.3) [ 32 , 42 ]. With increasing the amount of inorganic filler, water uptake, linear swelling ratio (dimensional stability), and IEC were increased.…”
Section: Resultsmentioning
confidence: 89%
“…The second weight loss was noted in the range of 180 to 240 °C. It was due to the degradation quaternary ammonium group into the polymeric material [ 32 , 33 ]. The final weight loss was found around 470 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the PPO-based porous membrane functionalized with quaternary ammonium groups ( Figure 7 e) without aromatic groups ( T d = 164.2 °C) [ 78 ], the membrane exhibited a higher thermal stability (thermal degradation temperature ( T d = 179 °C)). Besides, Khan [ 101 ] prepared a series of PPO-based AEMs modified by phenylimidazole groups ( Figure 7 f). The results showed that these AEMs exhibited excellent acid stability.…”
Section: Membrane Stabilitymentioning
confidence: 99%
“… The structure of ( a ) quaternizated poly(VBC-co-γ-MPS), ( b ) Q-DAN, ( c ) glycidyl trimethyl ammonium chloride, ( d ) quaternary aromatic amine groups, ( e ) quaternary ammonium, ( f ) phenyl imidazole, ( g ) AESP ( h ) QUDAP [ 49 , 78 , 83 , 84 , 99 , 100 , 101 , 102 ]. …”
Section: Figurementioning
confidence: 99%